Motivational factors for the adoption of ISO 9001 standards in Eastern Europe: The case of Bulgaria - Svetoslav Georgiev; Emil Georgiev (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: This study analyzes the motivational factors for ISO 9001 certification in Bulgaria from the internal/external motivations perspective, or the so-called dual model. Design/methodology/approach: This study is based on a mixed method research approach, which employed two interviews with experts in the field of quality management at the exploratory stage, and a survey involving 127 companies at the descriptive stage. Findings: This study claims that enhanced company image and competitiveness - an external motivation - is the leading motivational factor for ISO 9001 certification in Bulgaria. At the same time, our primary investigation reveals that Bulgarian firms are not predominantly externally driven, for internal motivations including process improvement and product quality improvement seem to be an important driver for ISO 9001 certification. Last but not least, this research asserts that enhanced company image and competitiveness has a stronger impact on the motivations for ISO 9001 certification than customer and supplier pressure, which is in line with previous research works on developing economy economies such as Bulgaria. Finally, our study indicates a moderate, yet positive correlation between motivations for and benefits of ISO 9001 certification. Social implications: This research work casts some light on the evolution of quality management in Bulgaria since the end of communism, which can serve as an important foundation for the better understanding of quality management in former communist economies in general and Eastern European states in particular. Originality/value: Derived from the acute gap between ISO studies in Western and former communist economies, this research work presents one of the first official, international studies in the field of ISO certification in Bulgaria, and more precisely, a paper describing the motives for ISO 9001 certification among Bulgarian businesses.
Keywords: 650; quality standards; ISO 9000 series; certification; motivational factors; benefits; quality management; Bulgaria